RETRACTED ARTICLE: Design of 3D animation color rendering system supported by cloud computing based on genetic algorithm - Ling, Yan (Soft computing (Berlin, Germany), 2023)
The wireless network is composed of multiple micronetwork nodes that are difficult to replace. These network nodes are usually located in areas with poor environmental conditions, so the energy consumption and security of nodes have become the main limitations and challenges. Therefore, this paper discusses the network topology, data transmission and node trust mechanism, and proposes a cloud computing technology algorithm for intelligent regional wireless network. According to the data of arrival delay difference in intelligent regional wireless network environment, the approximate location of mobile system is set as different positioning results. The dynamic position of the mobile system is obtained through multiple calculations. With the support of cloud computing technology, this paper also studies the color rendering system of 3D animation. 3D animation can not only express emotions and feelings, but also color render through the facial expressions of characters in the animation, so as to enhance the entertainment and interest visible to the audience. However, due to the great demand for computing resources and color rendering resources, at present, the main research and implementation are carried out on the desktop platform. There are also solutions to use high-end infrared devices for 3D animation color rendering on the mobile system. However, because this method has high cost in use and does not have universality on the mobile device, this paper proposes a rendering system suitable for the general mobile platform. This paper studies the 3D animation color rendering system based on wireless network cloud computing technology, hoping to realize the universality of the system with the support of technology.